Risk factors for coronary in-stent restenosis in Moroccan patients: a retrospective case-control study: Risk factors for coronary stent restenosis - El Mansouri, Rajaa; Habbal, Rachida (Cellular and Molecular Biology, 2025)
In-stent restenosis remains a significant challenge in interventional cardiology despite technological advancements. This retrospective case-control study conducted at the University Hospital Center Ibn Rochd in Casablanca (2020-2023) examined risk factors associated with coronary in-stent restenosis in 68 patients equally distributed between restenosis and no-restenosis groups. Diabetes emerged as a powerful predictor of restenosis (RR=4.15, 95% CI [1.05-16.4]), with notable differences in lipid profiles between groups. Restenosis patients exhibited significantly higher LDL cholesterol (2.19 vs. 1.31 mmol/L, p<0.001) and lower HDL levels. Univariate logistic regression identified multiple significant factors, including medication intake duration (OR=1.30, 95% CI [1.09-1.54], p=0.003) and LDL levels (OR=26.7, 95% CI [5.03-141.8], p<0.001). Dual antiplatelet therapy duration differed significantly between groups (p<0.001), while stent characteristics showed no significant differences. Our findings highlight diabetes mellitus as a critical determinant of coronary in-stent restenosis, operating synergistically with specific lipid abnormalities. These results underscore the need for targeted preventive strategies in diabetic patients undergoing percutaneous coronary intervention, including aggressive glycemic control, intensive lipid management, and optimized antiplatelet therapy regimens. The pronounced relationship between diabetes and restenosis emphasizes the importance of individualized approaches to coronary intervention in this high-risk population.